An age-stratified serosurvey against purified Salmonella enterica serovar Typhi antigens in the Lao People´s Democratic Republic. - Lisa Hefele; Antony P Black; Trinh Van Tan; Nguyen Tri Minh; Nguyen Duc Hoang; Siriphone Virachith; Claude P Muller; Judith M Hübschen; Paula Russell; Josefin Bartholdson Scott; Chau Nguyen Ngoc Minh; Tran Vu Thieu Nga; et al. (Public Library of Science (PLoS), 2021)
The epidemiology of typhoid fever in Lao People`s Democratic Republic is poorly defined. Estimating the burden of typhoid fever in endemic countries is complex due to the cost and limitations of population-based surveillance; serological approaches may be a more cost-effective alternative. ELISAs were performed on 937 serum samples (317 children and 620 adults) from across Lao PDR to measure IgG antibody titers against Vi polysaccharide and the experimental protein antigens, CdtB and HlyE. We measured the significance of the differences between antibody titers in adults and children and fitted models to assess the relationship between age and antibody titers. The median IgG titres of both anti-HylE and CdtB were significantly higher in children compared to adults (anti-HylE; 351.7 ELISA Units (EU) vs 198.1 EU, respectively; p<0.0001 and anti-CdtB; 52.6 vs 12.9 EU; p<0.0001). Conversely, the median anti-Vi IgG titer was significantly higher in adults than children (11.3 vs 3.0 U/ml; p<0.0001). A non-linear trend line fitted to the anti-CdtB and anti-HlyE IgG data identified a peak in antibody concentration in children <5 years of age. We identified elevated titers of anti-HlyE and anti-CdtB IgG in the serum of children residing in Lao PDR in comparison to adults. These antigens are associated with seroconversion after typhoid fever and may be a superior measure of disease burden than anti-Vi IgG. This approach is scalable and may be developed to assess the burden of typhoid fever in countries where the disease may be endemic, and evidence is required for the introduction of typhoid vaccines.